The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Accuracy of Determining the Coordinates Property Borders

Abstract: Property boundary points define the extent of property rightsin the field. For this reason, the precision of these coordinates is one of the most crucial factors which decide in both cases: the surface area of the property and the accuracy of this field and about the reliability limits and therefore the credibility of the cadastral system of the state. The ongoing process of cadastre modernization in Poland allows to improve the accuracy of the position of property boundary points. The coordinates of the bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…3). At the subject property, which was previously divided into 5 plots of land [1,2], the developer designed in the first version 8, and when he did not obtain the permission of the building permit, "6 single-family houses ... with two premises each" (Fig. 4).…”
Section: Investment Location and Local Social Conflictsmentioning
confidence: 99%
“…3). At the subject property, which was previously divided into 5 plots of land [1,2], the developer designed in the first version 8, and when he did not obtain the permission of the building permit, "6 single-family houses ... with two premises each" (Fig. 4).…”
Section: Investment Location and Local Social Conflictsmentioning
confidence: 99%
“…As part of the consolidation works, the boundaries of field invariants, that is, registration plots, whose layout and location remain unchanged (in accordance with the wishes of the consolidation participants) are also established [4]. It is important from the point of view of rational land use to change the spatial layout so as to improve the layout of farmsteads, parts of which are located on opposite sides of the motorway, so that access to them would be significantly longer.…”
Section: Correction Of the Layout Of Plots Through Mergementioning
confidence: 99%
“…According to art. 13 (4) in the event of failure to adopt the resolution referred to in para. 1, the district head, after considering the objections raised, seeking the opinion of experts and introducing possible changes, accepts the estimate of land, forests, orchards, gardens, hoppers and other special crops by means of an order subject to complaint.…”
Section: Estimating the Value Of Landmentioning
confidence: 99%
“…Taking into account technical standards for topographic surveys [28], it can be concluded that the data on the location of land use turn points should be captured using detailed surveys which ensure the accuracy of not less than 0.50 m relative to the nearest points of the horizontal geodetic control network and the measuring network. These requirements, of course, are significantly less restrictive than in the case of a numerical description of the boundaries of a cadastral parcel [29]. However, if the land use contour coincides with the parcel boundary, then it can be assumed that the mean error with which the location of the boundary point has been established, will also be identical for the turn point of the land use contour.…”
Section: Introductionmentioning
confidence: 99%